Symmetrization for mixed operators - Bahrouni, Sabri (Annales Mathematicae Silesianae, 2024)
In this paper, we prove Talenti’s comparison theorem for mixed local/nonlocal elliptic operators and derive the Faber–Krahn inequality for the first eigenvalue of the Dirichlet mixed local/nonlocal problem. Our findings are relevant to the fractional p&q−Laplacian operator.